DAMPAK ASIMETRI INFORMASI, ESOP, KUALITAS AUDIT TERHADAP MANAJEMEN LABA DENGAN VARIABLE PEMODERASI KESULITAN FINANSIAL - William Thamlim; Susi Dwi Mulyani (Media Riset Akuntansi, Auditing & Informasi, 2023)
The fundamental purpose of this research is to obtain empirical evidence about the influence of information asymmetry, Employee Stock Ownership Program (ESOP), and audit quality on the practice of earnings management using discretionary revenue components of manufacturing firms in Indonesia and examine the moderating effect of financial distress on these factors. Firms used as references are manufacturing companies in the basic materials, industrials, consumer non-cyclical, consumer cyclical, and healthcare pharmaceuticals sectors listed in the Indonesia Stock Exchange from 2019-2021. This study uses purposive sampling method with panel data moderation and obtains total of 546 sample data units. Based on the research conclusion, information asymmetry can trigger a higher risk of earnings management, while the existence of an ESOP and audit quality can be used to suppress earnings management. Financial distress itself has no direct effect on earnings management. Financial distress has not been proven to strengthen the positive influence of information asymmetry or weaken the negative influence of the ESOP. Meanwhile, the financial distress conditions can weaken the role of audit quality in an effort to minimize earnings management practices of the company.